2018
DOI: 10.1007/s00380-018-1181-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the wearable cardioverter-defibrillator (WCD) and WCD-based remote rhythm monitoring in a real-life patient cohort

Abstract: The wearable cardioverter-defibrillator (WCD) was introduced to provide protection from sudden cardiac death (SCD) in patients with transiently elevated risk or during ongoing risk stratification. Benefits and clinical characteristics of routine WCD use remain to be assessed in larger patient populations. This study aims to identify determinants of WCD compliance, therapies, and inappropriate alarms in a real-life cohort. A total of 106 cases (68.9% male) were included between 11/2010 and 04/2016. WCD therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 15 publications
4
17
2
Order By: Relevance
“…Additional non-validated questions revealed that the number of experienced WCD alarms influenced the fear of WCD shocks but no further dimensions. These results correspond with the results of the study of Zylla et al (54) who report no relationship between inadequate alarms and compliance ( r = .055, p = .578). As the study of Lackermair et al (44) had no comparator arm it remains unclear how patients without a WCD rate their QoL in a situation with a high risk for SCD and strong dependence on bystanders and their adequate reaction in the case of a SCA.…”
Section: Discussionsupporting
confidence: 91%
“…Additional non-validated questions revealed that the number of experienced WCD alarms influenced the fear of WCD shocks but no further dimensions. These results correspond with the results of the study of Zylla et al (54) who report no relationship between inadequate alarms and compliance ( r = .055, p = .578). As the study of Lackermair et al (44) had no comparator arm it remains unclear how patients without a WCD rate their QoL in a situation with a high risk for SCD and strong dependence on bystanders and their adequate reaction in the case of a SCA.…”
Section: Discussionsupporting
confidence: 91%
“…A study detailing three-year experience with WCDs, published from France, did not show any appropriate shocks and one inappropriate shock which is similar to the results we saw in a much smaller sample [13]. There was another study published out of Germany that analyzed six years of data and reported one appropriate and two inappropriate shocks [14].…”
Section: Discussionsupporting
confidence: 75%
“…Garcia et al reported similar results from the WEARIT-France trial, showing that younger age was the only factor that could be associated with a significant reduction in compliance in a multivariable analysis (odds ratio (OR) 0.97, 95% confidence interval (CI) 0.95-0.99; p < 0.01) [9]. Significantly lower wearing compliance in younger patients was also reported by Zylla et al from their evaluation of 106 WCD prescriptions [25]. In the analysis of Olgin et al, younger age also tended to be associated with lower wearing compliance, though the corresponding uniand multivariate analysis did not reveal a statistical significance [26].…”
Section: Discussionmentioning
confidence: 53%